2008
DOI: 10.1159/000114036
|View full text |Cite
|
Sign up to set email alerts
|

Open-Label Trial of Anti-TNF-α in Dermato- and Polymyositis Treated Concomitantly with Methotrexate

Abstract: Background/Aims: To determine the efficacy of infliximab combined with weekly methotrexate in drug-naive recent-onset dermatomyositis and polymyositis. Methods: A multicentre open-label controlled trial was conducted. Disease activity was assessed using patient’s and physician’s disease activity assessment, manual muscle testing (MMT), handheld dynamometry, and serum CK. The primary objective was to assess the efficacy using MMT after a period of 26 weeks. Results: The study was terminated prematurely because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(53 citation statements)
references
References 16 publications
(9 reference statements)
1
46
0
4
Order By: Relevance
“…The lack of improvement in muscle strength was associated with persistent signs of inflammation in muscle biopsies or on MRI of thigh muscles. Similar results were reported in an open-label trial of infliximab combined with weekly methotrexate in drug-naive patients [76], which was terminated prematurely because of a difficulty in recruiting cases, due to disease progression and the occurrence of adverse events. Thus, at present, the use of infliximab in patients with treatmentresistant myositis is not recommended.…”
Section: Infliximabsupporting
confidence: 81%
“…The lack of improvement in muscle strength was associated with persistent signs of inflammation in muscle biopsies or on MRI of thigh muscles. Similar results were reported in an open-label trial of infliximab combined with weekly methotrexate in drug-naive patients [76], which was terminated prematurely because of a difficulty in recruiting cases, due to disease progression and the occurrence of adverse events. Thus, at present, the use of infliximab in patients with treatmentresistant myositis is not recommended.…”
Section: Infliximabsupporting
confidence: 81%
“…TNF expression is detected within inXamed muscle in situ, and anti-TNF agents are sometimes used to treat intractable myositis [14,15]. Several investigators, including Hall et al, have reported cases of RA treated by anti-TNF agents in which myositis developed at a later point [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…While early case series reported positive effects [80][81][82][83][84][85][86], there has been increasing concern over these drugs due to some recent reports of disease flares or the initiation of myositis with TNF-α therapies [87][88][89][90]. An open-label study looking at the efficacy of infliximab combined with methotrexate was terminated owing to a low inclusion rate and a high dropout rate due to disease progression or side effects [91]. Another open-label study of infliximab performed in 13 patients with refractory DM/PM/IBM found no patients improved in muscle strength, measured by manual muscle testing, and several patients actually worsened [92].…”
Section: Cytokine-based Therapiesmentioning
confidence: 99%